Pengenalan Teknologi Artificial Intelligence Untuk Guru Dalam Peningkatan Pembelajaran Di SMA Alia Islamic School - Meidy Fajar Wahyu; Yuda Samudra; Lely Panca Andriyanto (CV. Multi Kreasi Media, 2025)
One aspect that supports teaching and learning activities in the 21st century is mastery of aspects of digital technology for the use of cyberspace. This is also explained in Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers that a teacher must have four competencies, namely pedagogical, personality, social and professional competencies. With this law, it is hoped that it will provide an opportunity for teachers to increase their professionalism through training held in scientific forums. However, there are several obstacles that teachers still face in improving their professionalism, one of which is mastery of technology. Artificial Intelligence (AI) is an application and a series of instructions related to programming where the results will look like from a human perspective. Apart from that, the reach of this technology has been used widely, including in the education sector. The implementation of AI in the education sector has had many positive impacts. Some of the positive impacts of applying AI in the education sector are increasing speaking, listening, reading and writing skills as well as the development of fun learning methods. This activity aims to explain the development of the Introduction of Artificial Intelligence Technology for Teachers in Improving Learning and its impact on modern society. We will look at the role of Artificial Intelligence in creating vibrant social networks, the emergence of leading social networking sites, and the shift from traditional media to social media. In addition, we will also discuss the concept of Artificial Intelligence and the potential it has in changing the way we search for and manage information. The introduction of Artificial Intelligence Technology for Teachers in Improving Learning at SMA ALIA Islamic School Tangerang, aims to enable teachers to be aware of developments in Artificial Intelligence technology, especially in today's digital world. The Community Service Team coordinates with the principal and deputy principal to hold activities for students at ALIA Islamic School.